2013
DOI: 10.1017/s1460396913000447
|View full text |Cite
|
Sign up to set email alerts
|

The role of the keyworker in breaking down professional culture barriers to providing high-quality palliative care: a literature review

Abstract: Background: Palliative cancer care is by definition multi-professional in nature. An interdisciplinary approach to disease management emphasising continuity of care results in increased quality of life for patients and families. Complex disease management demands the provision of a full spectrum of high-quality care; requiring both specialist and generalist services. Appointed keyworkers are knowledgeable about patient preferences enabling effective coordination of care and promotes collaborative team-working.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
(166 reference statements)
1
4
0
Order By: Relevance
“…Findings from the studies are mainly inconclusive regarding the role and responsibilities of the palliative care key worker. This scoping review supports the claim in previous research (Feuz, 2014) and editorial pieces (Berry, 2015) that gaps in understanding exist on the keyworker's role in palliative care. Further exploration and research are required to establish the role of key worker and how the role is allocated, implemented, and gauged to be effective within health systems.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Findings from the studies are mainly inconclusive regarding the role and responsibilities of the palliative care key worker. This scoping review supports the claim in previous research (Feuz, 2014) and editorial pieces (Berry, 2015) that gaps in understanding exist on the keyworker's role in palliative care. Further exploration and research are required to establish the role of key worker and how the role is allocated, implemented, and gauged to be effective within health systems.…”
Section: Discussionsupporting
confidence: 83%
“…Specifically: training, education, and clarification of the role. Feuz (2014) found that interdisciplinary collaboration was key to the provision of high-quality effective palliative care, however physicians are usually considered to be the ultimate decision makers (Bélanger et al, 2014). Feuz (2014) asserts that key workers are ideally placed to overcome professional culture barriers through facilitating improved communication within the interdisciplinary team.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(R16). This is of particular concern because inadequate communication with patients and avoidant behaviours have been shown to contribute to workplace burnout for individuals working in palliative care [14,15]. Therefore, improving communication through increased knowledge and positive attitudes toward PEOLC benefits not only patients and families, but also the individuals working with this patient population.…”
Section: Discussionmentioning
confidence: 99%
“…This lack of understanding can contribute to dismissive or avoidant behaviours that may have a negative impact on the quality of patient care provided [11,12]. In addition, attitudinal barriers can influence HCPs' willingness to engage in PEOLC [13]; hindering the provision of quality care [14][15][16]. Yet, individuals are not born with specific attitudes toward PEOLC.…”
Section: Introductionmentioning
confidence: 99%